N-Oxy lipid-based click chemistry for orthogonal coupling of mannan onto nanoliposomes prepared by microfluidic mixing: Synthesis of lipids, characterisation of mannan-coated nanoliposomes and in vitro stimulation of dendritic cells. (1st March 2019) - Bartheldyová, Eliška; Turánek Knotigová, Pavlína; Zachová, Kateřina; Mašek, Josef; Kulich, Pavel; Effenberg, Roman; Zyka, Daniel; Hubatka, František; Kotouček, Jan; Čelechovská, Hana; Héžová, Renata; Tomečková, Andrea; et al.
Highlights: Aminooxy lipids were designed and synthesized as click chemistry components for preparation of functionalised liposomes. Orthogonal binding of low MW mannan onto the liposome surface via click chemistry based on aminooxy ligation was proved. Mannan-coated liposomes prepared by microfluidic mixing and clic-chemistry stimulated dendritic cells Mannan-coated liposomes has a potential to be used as self-adjuvanted nanocarrier of construction of recombinant vaccines. Abstract: New synthetic aminooxy lipid was designed and synthesized as a building block for the formulation of functionalised nanoliposomes (presenting onto the outer surface of aminooxy groups) by microfluidic mixing. Orthogonal binding of cellular mannan (Candida glabrata (CCY 26-20-1) onto the outer surface of functionalised nanoliposomes was modified by orthogonal binding of reducing termini of mannans to oxime lipids via a click chemistry reaction based on aminooxy coupling (oxime ligation). The aminooxy lipid was proved as a suitable active component for preparation of functionalised nanoliposomes by the microfluidic mixing method performed with the instrument NanoAssemblr™. This "on-chip technology" can be easily scaled-up. The structure of mannan-liposomes was visualized by transmission and scanning electron microscopy, including immunogold staining of recombinant mannan receptor bound onto mannosylated-liposomes. The observed structures are in a good correlation with data obtained by DLS, NTA, and TPRS methods. In vitro experiments on human and mouse dendritic cells demonstrate selective internalisation of fluorochrome-labelled mannan-liposomes and their ability to stimulate DC comparable to lipopolysaccharide. We describe a potentially new drug delivery platform for mannan receptor-targeted antimicrobial drugs as well as for immunotherapeutics. Furthermore, the platform based on mannans bound orthogonally onto the surface of nanoliposomes represents a self-adjuvanted carrier for construction of liposome-based recombinant vaccines for both systemic and mucosal routes of administration.